Answer:
Step-by-step explanation:
= x²(-3 +5) +y²(2 -3) +5xy -2y
= 2x² -y² +5xy -2y
a) there are 4 terms in the simplified expression
b) 2 terms have negative coefficients (-y² and -2y)
Answe8 times 8 equal 69 and bla ba
Step-by-step explanation:
79 ft/s = 0.0240792 km/s
0.0240792 x 60 = 1.444752 km/minute
<span>1.444752 x 60 = </span><span>86.68512 km/hour
</span>
Ans: 86.69 km/h
Answer:
B
Step-by-step explanation:
It's not a function because the X's repeat
Answer:
x = - 2, x = - ![\frac{3}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D)
Step-by-step explanation:
Given
5x² + 1 = - 13x - 5 ( add 13x - 5 to both sides )
5x² + 13x + 6 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 5 × 6 = 30 and sum = 13
The factors are 10 and 3
Use these factors to split the x- term
5x² + 10x + 3x + 6 = 0 ( factor the first/second and third/fourth terms )
5x(x + 2) + 3(x + 2) = 0 ← factor out (x + 2) from each term
(x + 2)(5x + 3) = 0
Equate each factor to zero and solve for x
x + 2 = 0 ⇒ x = - 2
5x + 3 = 0 ⇒ 5x = - 3 ⇒ x = - ![\frac{3}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%7D)